Preparation method and application of carbon nitride / titanium carbide / amidoxime-based hydrogel
By using carbon nitride/titanium carbide/amidoxime-based hydrogel material, the 3D network structure and the amidoxime-based characteristics of PAN nanoparticles are used to solve the problems of low uranium extraction efficiency and poor material stability in seawater, and the uranium extraction effect is achieved with high efficiency, strong selectivity and good recycling.
Patent Information
- Application Number
- CN202411483531.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-23
- Publication Date
- 2025-03-28
AI Technical Summary
The prior art is difficult to efficiently extract uranium in seawater, especially in the presence of low uranium concentration and competitive ions and organic matter, and the stability and recycling of materials are also challenging.
Carbon nitride/titanium carbide/geminoxime-based hydrogel material is used to achieve efficient adsorption and photopromoting desorption uranium extraction through the 3D network structure of acrylamide and the amidoxime oxidation of PAN nanoparticles.
The uranium extraction effect is achieved in 30 minutes, which has good selectivity for uranium, stable morphology, and desorption of uranium can be achieved under light, improving the recycling life of the material.
Smart Images

Figure CN119701857A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a preparation method and application of a carbon nitride / titanium carbide / amidoxime-based hydrogel. Technical Background
[0002] Uranium is a key fuel for nuclear reactions, but leakage into the environment can also cause serious public health problems for humans. Exploring new strategies for simultaneous detection and extraction of uranium is essential for public health and environmental protection. In addition, due to the increasing consumption of terrestrial uranium resources, terrestrial uranium reserves are rapidly decreasing, and it is estimated that they can only provide fuel for the nuclear energy industry for less than a century. Therefore, it is urgent to obtain uranium resources through non-traditional means. The world's seawater contains about 4.5 billion tons of uranium, which is considered to be an inexhaustible uranium resource. However, the concentration of uranium in seawater is very low, and achieving batch uranium extraction is a huge challenge.
[0003] In recent years, photocatalytic materials, MOF and other materials have been proposed continuously, but the scope of their actual application scenarios is too narrow to meet the needs of actually putting them into seawater for uranium extraction. First, the uranium concentration in seawater is relatively low, and efficient adsorption materials are required to achieve economically feasible extraction. Secondly, there are a large number of competitive ions and organic substances in seawater, which may interfere with the adsorption process of uranium and reduce the extraction efficiency. In addition, the complexity of the seawater environment also leads to challenges in the stability and recyclability of materials, and performance degradation or failure may occur after long-term use.
[0004] Based on this, this invention provides a preparation method and application of carbon nitride / titanium carbide / amidoxime-based hydrogel. Summary of the invention
[0005] In view of the shortcomings of various existing hydrogel materials such as slow adsorption and difficult uranium desorption, the present invention aims to provide a seawater uranium extraction hydrogel material that can quickly adsorb, has a stable morphology, and can promote light desorption. In the preparation of carbon nitride / titanium carbide / amidoxime-based hydrogel, the acrylamide used can make the gel have a 3D network, which can disperse and fix a large number of PAN nanoparticles at the molecular level and provide a good hydrophilic channel for the passage of uranyl ions. After amidoximation, PAN nanoparticles can be converted into PAO, and the amidoxime group of PAO can quickly pair with uranyl ions to achieve efficient adsorption.
[0006] In order to achieve the above object, the present invention provides the following technical solution, the steps are as follows:
[0007] S1: Preparation of carbon nitride-titanium carbide composite material:
[0008] The TiC-CN composite material used here comes from the method proposed by Yuan et al. (Cyano-bridged Schottky junction of CN-TiC for enhanced photocatalyst TiC H2 evolution and tetracycline degradation. Applied Surface Science 583 (2022): 152515.).
[0009] 1) Mix TiC and urea in a molar ratio of 1:10 to 1:10000, grind them appropriately in an agate mortar containing an appropriate amount of methanol, and mix them evenly.
[0010] 2) The obtained solid is reacted at 450-650° C. for 1-5 hours to obtain a TiC-CN composite material.
[0011] S2: Preparation of PAN nanoparticles:
[0012] The PAN nanoparticles used here come from the method proposed by Jing et al. (Synthesis of amidoximated polyacrylonitrile nanoparticles / graphene composite hydrogel for selective uranium sorption from saline lake brine [J]. Chemical Engineering Journal, 2020, 391: 123553).
[0013] 1) Add 1-10 ml of acrylonitrile, 1-1000 mg of (NH4)2S2O8, and 2-800 mg of N,N-methylenebisacrylamide to 100 ml of deionized water, and disperse by ultrasonic until they are uniformly dispersed.
[0014] 2) The obtained solution is placed in an oil bath and heated at 40-60°C for 3-8 hours. The substance obtained by heating is PAN.
[0015] 3) The obtained PAN was washed with methanol and deionized water in sequence, and then dried at 40-60° C. to constant weight.
[0016] 4) After drying to constant weight, PAN is finely ground to obtain PAN nanoparticles, which can be suspended in water for at least 10 hours.
[0017] S3: Preparation of carbon nitride / titanium carbide / amidoxime-based hydrogel
[0018] 1) Dissolve acrylic acid and acrylamide in 1 ml to 50 ml of deionized water, and disperse them by ultrasonic to make them evenly dissolved. The molar ratio of acrylic acid to acrylamide is 1:1 to 1:50.
[0019] 2) Add potassium persulfate and N,N-methylenebisacrylamide to the solution of 1) and dissolve them uniformly by ultrasonication. The molar ratio of potassium persulfate to N,N-methylenebisacrylamide is 1:1 to 1:50.
[0020] 3) Add the prepared PAN nanoparticles and carbon nitride-titanium carbide into 1 ml to 50 ml of deionized water, mix and disperse evenly by ultrasonication, wherein the mass ratio of PAN to TiC-CN is 1:1 to 1:20.
[0021] 4) Slowly drip the mixed solution of PAN nanoparticles and TiC-CN composite materials in 3) into the solution in 2) under stirring. The solution is continuously magnetically stirred to be fully mixed.
[0022] 5) After uniform mixing, the solution was sucked into an aluminum box using a rubber-tipped dropper, and the box was sealed and placed in an oven at 40-90° C. for 2-50 h to prepare a PAN / TiC / CN hydrogel.
[0023] 6) Add the obtained hydrogel to a mixed solution of sodium carbonate and hydroxylamine hydrochloride, seal it and place it in an oven at 40-90°C for 2-50 hours to fully oxime it. The hydrogel after oxime is PAO / TiC / CN, named PTCH. The molar ratio of sodium carbonate to hydroxylamine hydrochloride is 1:1-1:20.
[0024] The above-mentioned carbon nitride / titanium carbide / amidoxime-based hydrogel can be used in uranium extraction from seawater.
[0025] Compared with the prior art, the present invention has the following beneficial effects:
[0026] 1) The drug used in the present invention is cheap, simple to synthesize, easy to control parameters, green, safe, pollution-free, and has a high yield;
[0027] 2) The synthesized hydrogel has a high uranium extraction efficiency, and can achieve nearly 70% uranium extraction effect in 30 minutes;
[0028] 3) It has good selectivity for uranium. Even in the presence of interfering ions, it can still achieve a uranium removal rate of about 80%;
[0029] 4) The morphology is stable. The gel structure has no obvious change and is not damaged after being immersed in water for more than 6 months.
[0030] 5) Light-promoted deuranization: It can be directly desorbed under strong light, eliminating the need for washing with detergent, which can improve the cycle life of the hydrogel to a certain extent. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following is a brief introduction to the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. Those of ordinary skill in the art can also obtain other drawings based on these drawings without creative work.
[0032] Figure 1 This is the XRD pattern of the product prepared in Example 1 of the present invention.
[0033] Figure 2 This is the SEM image of PTCH prepared in Example 1 of the present invention.
[0034] Figure 3 This is a photocatalytic stripping diagram of the product prepared in Example 1 of the present invention.
[0035] Figure 4 This is a graph showing the selective adsorption of uranium by the product prepared in Example 1 of the present invention in the presence of interfering ions.
[0036] Figure 5 3. It is the C / C0 diagram of the products prepared in Examples 1 and 2 of the present invention.
[0037] Figure 6 This is a C / C0 comparison chart of the product prepared in Comparative Example 1 of the present invention and the products prepared in Examples 1 and 2.
[0038] Figure 7 This is a C / C0 comparison chart of the product prepared in Comparative Example 2 of the present invention and the products prepared in Example 1 and Example 2.
[0039] Figure 8 This is a C / C0 comparison chart of the product prepared in Comparative Example 3 of the present invention and the products prepared in Examples 1 and 2.
[0040] Fig. 9 This is a C / C0 comparison chart of the product prepared in Comparative Example 4 of the present invention and the products prepared in Examples 1 and 2. DETAILED DESCRIPTION
[0041] Example 1
[0042] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the technical solutions in the embodiments of the present invention are clearly and completely described. Of course, the embodiments described are partial embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work belong to the protection scope of the present invention.
[0043] The present invention uses water as a solvent and a blank hydrogel as a carrier, on which a TiC-CN composite material and PAO are attached to carry out efficient uranium extraction.
[0044] The hydrogel proposed by the present invention also has the characteristic of light-promoted uranium removal.
[0045] S1: Preparation of carbon nitride-titanium carbide composites
[0046] The TiC-CN composite material used here comes from Yuan et al. (Cyano-bridged Schottky junction of CN-TiC for enhanced photocatalyst TiC H2 evolution and tetracycline degradation. Applied Surface Science 583 (2022): 152515.)
[0047] 1) TiC and urea are mixed in a molar ratio of 1:10 to 1:10000, ground appropriately in an agate mortar containing an appropriate amount of methanol, and mixed evenly.
[0048] 2) The obtained solid is reacted at 450-650° C. for 1-5 hours to obtain a TiC-CN composite material.
[0049] S2: Preparation of PAN Nanoparticles
[0050] The PAN nanoparticles used here come from the method proposed by Jing et al. (Synthesis of amidoximated polyacrylonitrile nanoparticles / graphene composite hydrogel for selective uranium sorption from saline lake brine [J]. Chemical Engineering Journal, 2020, 391: 123553).
[0051] 1) Add 1-10 ml of acrylonitrile, 1-1000 mg of (NH4)2S2O8, and 2-800 mg of N,N-methylenebisacrylamide to 100 ml of deionized water, and disperse by ultrasonic until they are uniformly dispersed.
[0052] 2) The obtained solution is placed in an oil bath and heated at 40-60°C for 3-8 hours. The substance obtained by heating is PAN.
[0053] 3) The obtained PAN was washed with methanol and deionized water in sequence, and then dried at 40-60° C. to constant weight.
[0054] 4) After drying to constant weight, PAN is finely ground to obtain PAN nanoparticles, which can be suspended in water for at least 10 hours.
[0055] S3: Preparation of carbon nitride / titanium carbide / amidoxime-based hydrogel
[0056] 1) Dissolve acrylic acid and acrylamide in 1 ml to 50 ml of deionized water, and disperse them by ultrasonic to make them evenly dissolved. The molar ratio of acrylic acid to acrylamide is 1:1 to 1:50.
[0057] 2) Add potassium persulfate and N,N-methylenebisacrylamide to the solution of 1) and dissolve them uniformly by ultrasonication. The molar ratio of potassium persulfate to N,N-methylenebisacrylamide is 1:1 to 1:50.
[0058] 3) Add the prepared PAN nanoparticles and carbon nitride-titanium carbide into 1 ml to 50 ml of deionized water, mix and disperse evenly by ultrasonication, wherein the mass ratio of PAN to TiC-CN is 1:1 to 1:20.
[0059] 4) Slowly drip the mixed solution of PAN nanoparticles and TiC-CN composite materials in 3) into the solution in 2) under stirring. The solution is continuously magnetically stirred to be fully mixed.
[0060] 5) After uniform mixing, the solution was sucked into an aluminum box using a rubber-tipped dropper, and the box was sealed and placed in an oven at 40-90° C. for 2-50 h to prepare a PAN / TiC / CN hydrogel.
[0061] 6) The obtained hydrogel is added to a mixed solution of sodium carbonate and hydroxylamine hydrochloride, sealed and placed in an oven at 40-90° C. for 2-50 hours to fully amine oxime to obtain a PAO / TiC / CN hydrogel named PTCH, wherein the molar ratio of sodium carbonate to hydroxylamine hydrochloride is 1:1-1:20.
[0062] Figure 1 is the XRD diagram of Example 1, Figure 2 This is the EDS graph of PTCH prepared in Example 1 after adsorbing uranium. It can be seen from the graph that uranium is successfully loaded on the hydrogel.
[0063] Add PTCH hydrogel to a uranium solution containing 0.01 g / L to 10 g / L. After adsorption for a period of time, irradiate with light. It can be seen that strong light causes uranium to desorb, such as Figure 3 shown.
[0064] When PTCH was added to simulated seawater, Ca, Co, Mg, and Zn solutions containing uranium, the adsorption of uranium by PTCH was stable at about 80% in various cases. Figure 4 shown.
[0065] Embodiment 2:
[0066] S1: Preparation of carbon nitride-titanium carbide composites
[0067] The method is consistent with that of Example 1.
[0068] S2: Preparation of PAN Nanoparticles
[0069] The method is consistent with that of Example 1.
[0070] S3: Preparation of carbon nitride / titanium carbide / amidoxime-based hydrogel
[0071] The method is basically the same as that of Example 1, wherein the mass of the PAN nanoparticles and the TiC-CN composite material used in step 3) is 4 times that of Example 1, and the obtained hydrogel is PTCH-4.
[0072] Figure 5 1 is a C / C0 diagram of uranium adsorption by Example 1 and Example 2. It can be seen that in terms of adsorption capacity, the two are basically the same, but the adsorption rate of PTCH is slightly faster than that of PTCH-4.
[0073] Comparative Example 1:
[0074] S1: Preparation of PAN nanoparticles
[0075] The method is consistent with that of Example 1.
[0076] S2: Preparation of g-C3N4
[0077] 1) Grind a certain amount of urea thoroughly, put it in a covered crucible, and place it in a muffle furnace for calcination.
[0078] 2) Heat from room temperature to 500°C at a heating rate of 5°C / min, calcine at 500°C for 2h, cool naturally after heating, and grind thoroughly.
[0079] S3: Preparation of carbon nitride / amidoxime-based hydrogels
[0080] Basically the same as Example 1, characterized in that the materials used in step 3) are PAN nanoparticles and g-C3N4, the required mass ratio thereof is 1:1 to 1:20, and the obtained hydrogel is PCNH.
[0081] Figure 6 The C / C0 diagram of uranium adsorption by Example 1 and Comparative Example 1 is shown. It can be seen that PCNH is lower than PTCH in terms of adsorption rate, and lower than PTCH and PTCH-4 in terms of adsorption capacity.
[0082] Comparative Example 2
[0083] S1: Preparation of PAN nanoparticles
[0084] The method is consistent with that of Example 1.
[0085] S2: Preparation of titanium carbide / amidoxime-based hydrogel
[0086] The method is basically the same as Example 1, characterized in that the materials used in step 3) are PAN nanoparticles and TiC, the required mass ratio of which is 1:1 to 1:20, and the obtained hydrogel is PTIH.
[0087] Figure 7 The C / C0 graphs of uranium adsorption by Example 1, Example 2 and Comparative Example 2 are shown. It can be seen that PTIH is slightly lower than PTCH and PTCH-4 in terms of both adsorption capacity and adsorption speed.
[0088] Comparative Example 3
[0089] S1: Preparation of PAN nanoparticles
[0090] The method is consistent with that of Example 1.
[0091] S2: Preparation of PAN hydrogel
[0092] It is basically the same as step S3 in Example 1, characterized in that the material used in step 3) is PAN nanoparticles, the required mass ratio is 20-60 mg, and there is no need to perform amine oximation. The obtained hydrogel is named PANH.
[0093] Figure 8 The C / C0 graphs of uranium adsorption by Example 1, Example 2 and Comparative Example 3 are shown. It can be seen that PANH is much lower than PTCH and PTCH-4 in terms of both adsorption capacity and adsorption speed.
[0094] Comparative Example 4
[0095] S1: Preparation of carbon nitride-titanium carbide composites
[0096] The method is consistent with that of Example 1.
[0097] S2: Preparation of TiC-CN hydrogel
[0098] The method is basically consistent with step S3 in Example 1, characterized in that the material used in step 3) is a TiC-CN composite material with a required mass ratio of 20 to 60 mg, and no amidoximation is required. The obtained hydrogel is named TCNH.
[0099] Fig. 9The C / C0 diagram of uranium adsorption by Example 1, Example 2 and Comparative Example 3. It can be seen that TCNH is much lower than PTCH and PTCH-4 in terms of both adsorption capacity and adsorption speed.
[0100] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0101] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.
Claims
1. A method for preparing a carbon nitride / titanium carbide / amidoxime-based hydrogel, comprising the following steps:
1. Preparation of carbon nitride-titanium carbide composite materials The TiC-CN composite material used here is from Yuan et al. (Cyano-bridged Schottky junction of CN-TiC for enhanced photocatalyst TiC H2 evolution and tetracycline degradation.Applied Surface Science 583(2022):152515.) 1) TiC and urea are mixed in a molar ratio of 1:10 to 1:10000, and ground appropriately in an agate mortar containing an appropriate amount of methanol to mix evenly. 2) The obtained solid is reacted at 450-650° C. for 1-5 hours to obtain a TiC-CN composite material.
2. Preparation of PAN Nanoparticles The PAN nanoparticles used here come from the method proposed by Jing et al. (Synthesis of amidoximated polyacrylonitrile nanoparticles / graphene composite hydrogel for selective uranium sorption from saline lake brine [J]. Chemical Engineering Journal, 2020, 391: 123553). 1) Add 1-10 ml of acrylonitrile, 1-1000 mg of (NH4)2S2O8, and 2-800 mg of N,N-methylenebisacrylamide to 100 ml of deionized water, and disperse by ultrasonic until they are uniformly dispersed. 2) The obtained solution is placed in an oil bath and heated at 40-60°C for 3-8 hours. The substance obtained by heating is PAN. 3) The obtained PAN was washed with methanol and deionized water in sequence, and then dried at 40-60° C. to constant weight. 4) After drying to constant weight, PAN is finely ground to obtain PAN nanoparticles, which can be suspended in water for at least 10 hours.
3. Preparation of carbon nitride / titanium carbide / amidoxime-based hydrogel 1) Dissolve acrylic acid and acrylamide in 1ml to 50ml of deionized water and disperse them by ultrasonic to make them dissolve evenly. The molar ratio of acrylic acid to acrylamide is 1:1 to 1:
50. 2) Add potassium persulfate and N,N-methylenebisacrylamide to the solution in 1) and dissolve them uniformly by ultrasonication, wherein the molar ratio of potassium persulfate to N,N-methylenebisacrylamide is 1:1 to 1:
50. 3) Add the PAN nanoparticles and carbon nitride-titanium carbide composite material prepared above into 1 ml to 50 ml of deionized water, mix and disperse evenly by ultrasonication, wherein the mass ratio of PAN to TiC-CN composite material required is 1:1 to 1:
20. 4) Slowly drip the mixed solution of PAN nanoparticles and TiC-CN composite materials in 3) into the solution in 2) under stirring. The solution is continuously magnetically stirred to be fully mixed. 5) After uniform mixing, the solution was sucked into an aluminum box using a rubber-tipped dropper, and the box was sealed and placed in an oven at 40-90° C. for 2-50 h to prepare a PAN / TiC / CN hydrogel. 6) The obtained hydrogel is added to a mixed solution of sodium carbonate and hydroxylamine hydrochloride, sealed and placed in an oven at 40-90°C for 2-50 hours to fully amine oxime. After the amine oxime is complete, the prepared hydrogel is PAO / TiC / CN, named PTCH. The molar ratio of sodium carbonate to hydroxylamine hydrochloride is 1:1-1:20.
Citation Information
Cited By
Amidoximation g-C3N4 / ZrO2 adsorbent, preparation method and application thereof, and uranium extraction method
CN117101620A
An amidoximated g-C3N4 / ZrO2 adsorbent, its preparation method and application, and uranium extraction method
CN117101620B